Full-length transcriptome sequencing and comparative transcriptome analysis of Eriocheir sinensis in response to infection by the microsporidian Hepatospora eriocheir - Hou, Libo; Wang, Mengdi; Zhu, Lei; Ning, Mingxiao; Bi, Jingxiu; Du, Jie; Kong, Xianghui; Gu, Wei; Meng, Qingguo (Frontiers in Cellular and Infection Microbiology, 2022)
As a new generation of high-throughput sequencing technology, PacBio Iso-Seq technology (Iso-Seq) provides a better alternative sequencing method for the acquisition of full-length unigenes. In this study, a total of 22.27 gigabyte (Gb) subread bases and 128,614 non-redundant unigenes (mean length: 2,324 bp) were obtained from six main tissues of Eriocheir sinensis including the heart, nerve, intestine, muscle, gills and hepatopancreas. In addition, 74,732 unigenes were mapped to at least one of the following databases: Non-Redundant Protein Sequence Database (NR), Gene Ontology (GO), Kyoto Encyclopaedia of Genes and Genomes (KEGG), KEGG Orthology (KO) and Protein family (Pfam). In addition, 6696 transcription factors (TFs), 28,458 long non-coding RNAs (lncRNAs) and 94,230 mRNA-miRNA pairs were identified. Hepatospora eriocheir is the primary pathogen of E. sinensis and can cause hepatopancreatic necrosis disease (HPND); the intestine is the main target tissue. Here, we attempted to identify the key genes related to H. eriocheir infection in the intestines of E. sinensis. By combining Iso-Seq and Illumina RNA-seq analysis, we identified a total of 12,708 differentially expressed unigenes (DEUs; 6,696 upregulated and 6,012 downregulated) in the crab intestine following infection with H. eriocheir. Based on the biological analysis of these DEUs, several key processes were identified, including energy metabolism-related pathways, cell apoptosis and innate immune-related pathways. Twelve selected genes from these DEUs were subsequently verified by quantitative real-time PCR (qRT-PCR) analysis. Our findings enhance our understanding of the E. sinensis transcriptome and the specific association between E. sinensis and H. eriocheir infection.